Evaluation of the efficacy of post prostatic massage urine cytology in diagnosis of various prostatic lesions with cytohistological and clinical correlation - Monisha Choudhury; Savita Agarwal (Journal of Cytology, 2017)
Background: Elderly men are at high risk of various prostatic diseases carrying high morbidity and mortality rates. For screening large populations, there is a need for a simple, reliable, and noninvasive test with high sensitivity and specificity. Exfoliated prostatic cancer cells can be harvested by prostatic massage and subjected to cytologic examination and molecular tests. Aims: This study was undertaken to evaluate the morphology of various prostatic lesions on post prostatic massage urine cytology and correlate cytologic, histologic, and clinical findings. It was further proposed to establish the diagnostic accuracy of post prostatic massage urine cytology in different prostatic lesions. Materials and Methods: Totally, 100 cases including 50 cases each from study group and control group were subjected to post prostatic massage urine cytology and correlated with clinical and histological findings. Results: Five out of 50 cases were diagnosed as prostatic carcinoma, of which 60% were clinically detected. Diagnostic accuracy by histology and cytology independently was 80%, and 20% remained false negative by each technique. On combining both the techniques, diagnostic accuracy was 100%. For nine cases each of prostatitis and nodular hyperplasia diagnosed clinically, the diagnostic accuracy by cytology was 100 and 66.6%, respectively. 62% (31) cases were diagnosed as nodular hyperplasia including 22 (44%) cases of nodular hyperplasia with prostatitis. Conclusion: Collection of urinary specimens after prostatic massage provides adequate samples for cytological examination and carries great importance in establishing the preoperative morphologic diagnosis in cases of malignancy, prostatitis, and prostatic calculi.